2015
DOI: 10.1021/acs.jafc.5b01026
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Potent Cysteine-Containing Dipeptide Inhibitors against Tyrosinase: A Comprehensive Investigation of 20 × 20 Dipeptides in Inhibiting Dopachrome Formation

Abstract: Tyrosinase is an essential copper-containing enzyme required for melanin synthesis. The overproduction and abnormal accumulation of melanin cause hyperpigmentation and neurodegenerative diseases. Thus, tyrosinase is promising for use in medicine and cosmetics. Our previous study identified a natural product, A5, resembling the structure of the dipeptide WY and apparently inhibiting tyrosinase. Here, we comprehensively estimated the inhibitory capability of 20 × 20 dipeptides against mushroom tyrosinase. We fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 49 publications
3
30
0
Order By: Relevance
“…CRY and RCY used the thiol group of the cysteine residue to coordinate with Cu ions at the active site of tyrosinase, thereby showing low tyrosinase activity. In another study, the cysteine-containing dipeptides were reported to inhibit the tyrosinase activity in an effective manner 110 . The authors suggested that these cysteine-containing dipeptides could directly block the active site of tyrosinase and thereby leading to potent inhibition.…”
Section: Mushroom Tyrosinase Inhibitorsmentioning
confidence: 99%
“…CRY and RCY used the thiol group of the cysteine residue to coordinate with Cu ions at the active site of tyrosinase, thereby showing low tyrosinase activity. In another study, the cysteine-containing dipeptides were reported to inhibit the tyrosinase activity in an effective manner 110 . The authors suggested that these cysteine-containing dipeptides could directly block the active site of tyrosinase and thereby leading to potent inhibition.…”
Section: Mushroom Tyrosinase Inhibitorsmentioning
confidence: 99%
“…It may also be related to Parkinson’s disease and cancer. 4,7 Thus, tyrosinase inhibition is of interest in the food, medicine and cosmetics fields.…”
Section: Introductionmentioning
confidence: 99%
“…L -Tyr was stimulatory, while D -Tyr and L -Cys were inhibitory to melanin synthesis in cells [ 76 , 84 , 92 ]. Many Cys-containing compounds, such as glutathione, inhibited TYR-catalyzed melanin synthesis by acting as a reactant for the thiol conjugation reaction with DOPAquinone as well as acting as an enzyme inhibitor [ 87 , 88 , 89 ]. A number of peptides from synthetic peptide libraries or natural sources exhibited inhibitory effects against TYR activity in vitro, and some showed antimelanogenic effects at the cell level [ 90 , 101 , 102 , 103 , 104 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dipeptides GD, GK, and GH diminished the browning of fresh Golden Delicious apples and Irish White Skinned potatoes. Tseng et al estimated the inhibitory capacity of 20 × 20 dipeptides against mushroom TYR [ 87 ]. Cys-containing dipeptides exhibited highly potent TYR inhibition, and N-terminal Cys-containing dipeptides, such as CE (IC 50 = 2.0 μM), outperformed C-terminal Cys-containing dipeptides.…”
Section: Artificial Downregulation Of Melanin Synthesismentioning
confidence: 99%